Trichobezoar in young Nepalese girl with Rapunzel syndrome: A case report (Bangladesh Journal of Medicine, 2021)
Trichobezoar is a gastric foreign body that is composed of the patient’s own hair in the stomach. Rapunzel syndrome is an unusual form of trichobezoar in stomach,which extends into any part of the small intestine.We are reporting the case of gastric trichobezoar with thin tail extending into the duodenum in a twenty year oldgirl. She had a history of trichophagia. She presented with epigastric pain and vomiting. Endoscopic removal was attempted but this was unsuccessful. Subsequently the patient underwent exploratory laparotomy and gastrotomy.She recovered well and was discharged with advice for psychiatric consultation.Bangladesh J Medicine January 2021; 32(1) : 69-72